THE ANALYSIS OF FIRM FINANCIAL PERFORMANCE INFLUENCE TOWARDS ECO-INNOVATION ON INDONESIAN CONSUMER GOODS COMPANIES - Diah Permata Sari; Retno Kusumastuti (Faculty of Economics and Business, Hasanuddin University, Makassar, Indonesia, 2018)
Study about eco-innovation in Indonesia still very rare due to regulation that relatively new in governance of the firm. This paper elaborates the correlation between proxy of eco-innovation and financial firm performance. Eco-innovation is a term that refers to innovation activities conducted by the firm with ecological perspective based. Deductive methodology is being used to confirmatory the correlation between variables. This research examines the influence of firm financial performance towards eco-innovation. In particular, this research discusses firm financial performance which proxies by Return on Asset (ROA), Return on Equity (ROE), and Earning Retention Ratio (ERR) that could affects firms on making a decision about Eco-Innovation. This research used 155 firm years observation that consist of 31 consumer goods companies listed in Indonesian Stock Exchange during the period 2011-2015. From the total observation showed that 75 firm years perform Eco-Innovation and 80 firm years did not perform Eco-Innovation. The test is conducted by using logit regression model. The results of this study are ROA has a significant and negative impact toward Eco-Innovation, ROE has a significant positive impact on Eco-Innovation, and ERR has no significant impact on Eco-Innovation.